Variations on the Canon : Essays on Music from Bach to Boulez in Honor of Charles Rosen on His Eightieth Birthday - Macleod, Catriona; Purdy, Daniel (Book collections on Project MUSE., 2010)
The Goethe Yearbook is a publication of the Goethe Society of North America, publishing original English-language contributions to the understanding of Goethe and other authors of the Goethezeit, while also welcoming contributions from scholars around the world. Goethe Yearbook 17 covers the full range of the era, from Karl Guthke's essay on the early Lessing to Peter Hoeyng's on Grillparzer. Notable is a special section, co-edited by Clark Muenzer and Karin Schutjer, that samples some of the exciting new work presented at the Goethe Society conference in November 2008: 200 years after the publication of Faust I, eight essays offer fresh views of this epic masterpiece, often through novel and surprising connections. Authors link for example Faust's final ascension and the circulation of weather, verse forms in the drama and the performance of national identity, the fate of Gretchen and the occult politics of Francis Bacon. Other papers explore epistemological structures and taxonomies at work in Goethe's prose, essays, and scientific writings. Contributors: Frederick Amrine, Johannes Anderegg, Matthew Bell, Benjamin Bennett, Gerrit Bruening, Christian Clement, Pamela Currie, Ulrich Gaier, Karl Guthke, Stefan Hajduk, Peter Hoeyng, Clark Muenzer, Andrew Piper, Herb Rowland, Heather Sullivan, Chad Wellmon, Ellwood Wiggins, Markus Wilczek. Daniel Purdy is Associate Professor of German at Pennsylvania State University. Book review editor Catriona MacLeod is Associate Professor of German at the University of Pennsylvania.